Methane combustion over Pd/CoAl2O4/Al2O3 catalysts prepared by galvanic deposition. Issue 55 (11th July 2017) - Mahara, Yuji; Tojo, Takumi; Murata, Kazumasa; Ohyama, Junya; Satsuma, Atsushi
Abstract : Pd/CoAl2 O4 /Al2 O3 methane combustion catalysts were synthesized using a galvanic deposition (GD) method (PdCoAl-GD). Abstract : Pd/CoAl2 O4 /Al2 O3 methane combustion catalysts were synthesized using a galvanic deposition (GD) method (PdCoAl-GD). This PdCoAl-GD catalyst showed higher activities and turnover frequencies (TOFs) than conventional Pd/Al2 O3 . According to X-ray diffraction (XRD), X-ray absorption fine structure (XAFS) and scanning transmission electron microscopy (STEM) measurements, PdCoAl-GD was composed of a CoAl2 O4 phase supported on γ-Al2 O3 and dispersed Pd nanoparticles of 2–7 nm in size on CoAl2 O4 . Operando Pd K-edge XAFS measurements indicated that the Pd in PdCoAl-GD was oxidized to highly active methane combustion PdO species at low temperatures. PdCoAl-GD also showed high activity (light-off tests) when PdO was initially present on the catalysts. Methane temperature-programmed reaction (CH4 -TPR) measurements on PdCoAl-GD revealed that PdO was reduced by CH4 at low temperatures. The GD method used herein achieved PdO species that were effective for C–H activation.